A modern network approach to revisiting the positive and negative affective schedule (PANAS) construct validity - Flores Kanter, Pablo Ezequiel (2021)
Introduction: The factor structure of the Positive and Negative Affective Schedule (PANAS) is still a topic of debate. There are several reasons why using Exploratory Graph Analysis (EGA) for scale validation is advantageous and can help understand and resolve conflicting results in the factor analytic literature. Objective: The main objective of the present study was to advance the knowledge regarding the factor structure underlying the PANAS scores by utilizing the different functionalities of the EGA method. EGA was used to (1) estimate the dimensionality of the PANAS scores, (2) establish the stability of the dimensionality estimate and of the item assignments into the dimensions, and (3) assess the impact of potential redundancies across item pairs on the dimensionality and structure of the PANAS scores. Method: This assessment was carried out across two studies that included two large samples of participants. Results and Conclusion: In sum, the results are consistent with a two-factor oblique structure.